Analisis Perkembangan Moral Terhadap Perilaku Prososial Remaja Akhir - Ira Shapira Lado; Luh Putu Ruliati; Yeni Damayanti; Dian Lestari Anakaka (Universitas Nusa Cendana, 2019)
This research is a correlational study using a quantitative approach. This study correlates variables of moral development with prosocial behavior. Moral development is a development that related to one's ability to judge what should be done and not done in accordance with the norms that develop in society and prosocial behavior is behavior that sharing, helping, honest, generous and behavior considering the rights and welfare of others. The purpose of this study is to find out whether there is a relationship between moral development and prosocial behavior in late adolescents in the Oesapa Village of Kupang. This study involved 360 late adolescents. The research sampling technique uses random sampling techniques. Hypothesis testing uses Pearson product-moment correlation to examine the relationship of variables and their level of significance, furthermore, the results of the analysis obtained are correlation coefficients -0.054 with significance showing results of 0.303 (p> 0.05) which means there is no relationship between moral development and prosocial behavior in adolescents finally in Oesapa Village, Kupang.